Implicit Review Instrument to Evaluate Quality of Care Delivered by Physicians to Children in Emergency Departments. (16th November 2017) - Marcin, James P.; Romano, Patrick S.; Dharmar, Madan; Chamberlain, James M.; Dudley, Nanette; Macias, Charles G.; Nigrovic, Lise E.; Powell, Elizabeth C.; Rogers, Alexander J.; Sonnett, Meridith; Tzimenatos, Leah; Alpern, Elizabeth R.; et al.
Abstract : Objective: To evaluate the consistency, reliability, and validity of an implicit review instrument that measures the quality of care provided to children in the emergency department (ED). Data Sources/Study Setting: Medical records of randomly selected children from 12 EDs in the Pediatric Emergency Care Applied Research Network (PECARN). Study Design: Eight pediatric emergency medicine physicians applied the instrument to 620 medical records. Data Collection/Extraction Methods: We determined internal consistency using Cronbach's alpha and inter‐rater reliability using the intraclass correlation coefficient (ICC). We evaluated the validity of the instrument by correlating scores with four condition‐specific explicit review instruments. Principal Findings: Individual reviewers' Cronbach's alpha had a mean of 0.85 with a range of 0.76–0.97; overall Cronbach's alpha was 0.90. The ICC was 0.49 for the summary score with a range from 0.40 to 0.46. Correlations between the quality of care score and the four condition‐specific explicit review scores ranged from 0.24 to 0.38. Conclusions: The quality of care instrument demonstrated good internal consistency, moderate inter‐rater reliability, high inter‐rater agreement, and evidence supporting validity. The instrument could be useful for systems' assessment and research in evaluating the care delivered to children in the ED.